Iridium single-atom catalyst on nitrogen-doped carbon for formic acid oxidation synthesized using a general host–guest strategy - Li, Zhi; Chen, Yuanjun; Ji, Shufang; Tang, Yan; Chen, Wenxing; Li, Ang; Zhao, Jie; Xiong, Yu; Wu, Yuen; Gong, Yue; Yao, Tao; Liu, Wei; et al. (Nature chemistry, 2020)
Single-atom catalysts not only maximize metal atom efficiency, they also display properties that are considerably different to their more conventional nanoparticle equivalents, making them a promising family of materials to investigate. Herein we developed a general host–guest strategy to fabricate various metal single-atom catalysts on nitrogen-doped carbon (M 1 /CN, M = Pt, Ir, Pd, Ru, Mo, Ga, Cu, Ni, Mn). The iridium variant Ir 1 /CN electrocatalyses the formic acid oxidation reaction with a mass activity of 12.9 A mg Ir − 1 whereas an Ir/C nanoparticle catalyst is almost inert (~4.8 × 10 −3